Potentilla anserina L. developmental changes affect the rhizosphere prokaryotic community - Yaqiong Wang (Nature Portfolio, 2021)
Abstract Plant roots and soil prokaryotes primarily interact with each other in the rhizosphere. Changes in the rhizosphere prokaryotic structure are influenced by several factors. In this study, the community structure of the Potentilla anserina L. rhizosphere prokaryotes was identified and evaluated by high-throughput sequencing technology in different continuous cropping fields and developmental stages of the plant. In total, 2 archaeal (Euryarchaeota and Thaumarchaeota) and 26 bacterial phyla were identified in the P. anserina rhizosphere. The bacterial community was mainly composed of Acidobacteria, Actinobacteria, Bacteroidetes, Chloroflexi, Gemmatimonadetes, Planctomycetes, Proteobacteria, and Verrucomicrobia. Moreover, the prokaryotic community structure of the rhizosphere varied significantly during plant development. Our results provide new insights into the dynamics of the P. anserina rhizosphere prokaryotic community and may provide useful information for enhancing the growth and development of P. anserina through artificial control of the soil prokaryotes.